2016
DOI: 10.7567/apex.9.041102
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and polarization of stable phases of (Ga1− xInx)2O3

Abstract: The full phase diagram of (Ga1− x In x )2O3 is obtained theoretically. The phases competing for the ground state are monoclinic β (low x), hexagonal (x ∼ 0.5), and bixbyite (large x). Three disconnected mixing regions interlace with two distinct phase-separation regions, and at x ∼ 0.5, the coexistence of hexagonal and β alloys with phase-separated binary components is expected. We also explore the permanent polari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 16 publications
(30 reference statements)
1
75
0
2
Order By: Relevance
“…In a recent reappraisal of Roy's work, Playford et al reported a total neutron diffraction investigation of these polymorphs. 12 According to first principle calculations, 9,13 the ε-phase is the second most stable polymorph after β. In the last years the growth of single-phase ε-Ga 2 O 3 thin films was demonstrated on commercial sapphire as well as other hexagonal or pseudo-hexagonal substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent reappraisal of Roy's work, Playford et al reported a total neutron diffraction investigation of these polymorphs. 12 According to first principle calculations, 9,13 the ε-phase is the second most stable polymorph after β. In the last years the growth of single-phase ε-Ga 2 O 3 thin films was demonstrated on commercial sapphire as well as other hexagonal or pseudo-hexagonal substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the frequency of reports on the orthorhombic κ-modification (sometimes also referred to as ε-Ga2O3) is rapidly increasing lately. Among the polymorphs of Ga2O3, this is the only crystalline phase expected to exhibit a spontaneous electrical polarization along its c-direction that is predicted to surpass even the one of GaN by one order of magnitude (23 µC/cm 2 ) [5][6][7][8] . The latter is the reason for the tremendously increasing interest in this phase.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes a disordered structure with P6 3 mc space-group symmetry is labeled as ε-Ga 2 O 3 , which is comprised of domains of an ordered phase labeled κ-Ga 2 O 3 that is the same as the ordered orthorhombic ε-Ga 2 O 3 with Pna2 1 space-group symmetry [16]. These four phases are considered metastable [17,18], but the α- [19,20], γ - [21][22][23], and ε-Ga 2 O 3 [24][25][26] phases can be grown on various kinds of substrates. In particular, α-Ga 2 O 3 has been studied as a wide-gap semiconductor.…”
Section: Introductionmentioning
confidence: 99%